De Grote Methodiekengids definitie • inventarisatie • praktische toepasbaarheid • wetenschappelijke onderbouwing van begeleidingsmethodieken voor mensen met een verstandelijke beperking - Dekker, Alain; IJpma, Irene; Martens, Martha (University of Groningen Press, 2024)
To improve the quality of care, guidance methodologies can be very helpful for supervisors, practitioners and other stakeholders. A counseling methodology provides an employee with a shared view and concrete tools to act more systematically. This enhances acting skills and helps to better respond to specific needs and wishes of clients. This makes working according to methods one of the ways for professionalization. But what exactly is a counseling methodology? Which ones exist in the Netherlands? And for which target groups have they been developed? On the basis of ten criteria, 28 counseling methods were found and summarized. De Grote Methodiekengids, the result of two years of research by Alliade's Department of Applied Scientific Research (PWO), helps to make a choice for each target group on the basis of practical applicability and scientific foundation, among other things. This independent guide is indispensable for supervisors, policy makers, administrators, managers, researchers, remedial educationalists and psychologists in intellectual disability care. De Grote Methodiekengids compiles the available information from public sources and prevents each care facility from having to do comparative methodology research all over again.